2011
DOI: 10.1891/1058-1243.20.4.188
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Breastfeeding Duration Related to Maternal Attitudes in a Taiwanese Sample

Abstract: The purpose of this study was to examine maternal attitudes and sociodemographic variables associated with Taiwanese mothers' continuation of breastfeeding at 6 weeks postpartum. A sample of 140 in-hospital breastfeeding mothers was recruited in Taiwan. Participants completed the Iowa Infant Feeding Attitude Scale (IIFAS) in the hospital prior to discharge. Postdischarge participants were contacted by telephone at 3 and 6 weeks postpartum to obtain information regarding their feeding method and duration. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
2
19
3
4
Order By: Relevance
“…However, similar or lower proportions have been reported from middle-and lower-income countries specifically from the sub-Sahara African countries [21][22][23][24] . More than two-thirds, (69%), reported insufficient milk to be the main reason for not breastfeeding exclusively; a reason that has been cited earlier elsewhere [25][26] . In this study, education level of mothers and attitude towards exclusive breastfeeding were identified to be independent predictors of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 75%
“…However, similar or lower proportions have been reported from middle-and lower-income countries specifically from the sub-Sahara African countries [21][22][23][24] . More than two-thirds, (69%), reported insufficient milk to be the main reason for not breastfeeding exclusively; a reason that has been cited earlier elsewhere [25][26] . In this study, education level of mothers and attitude towards exclusive breastfeeding were identified to be independent predictors of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 75%
“…Attitudes toward breastfeeding were positively infl uenced by the media promotion campaign. Taiwan Public Television Service toward breastfeeding and exposure to breastfeeding (Ho &McGrath, 2011;Losch, Dungy, Russell, & Dusdieker, 1995;Marrone et al, 2008). This study aimed to further understand the breastfeeding attitudes among adolescents by gathering survey data from high school and vocational school men and women.…”
Section: Discussionmentioning
confidence: 99%
“…10 The campaigns addressed knowledge gaps and perceptions such as 'insufficient milk' that were shown in diverse cultural and development settings to influence breastfeeding practices. 11,12 Program evaluations have shown how programs to improve health services such as the Baby Friendly Hospital Initiative (BFHI) can improve breastfeeding practices. 13 However, only a few well documented studies are available on the impact of mass media on IYCF.…”
Section: Introductionmentioning
confidence: 99%